2019
DOI: 10.7150/jca.30376
|View full text |Cite
|
Sign up to set email alerts
|

On The Role of Myelin and Lymphocyte Protein (MAL) In Cancer: A Puzzle With Two Faces

Abstract: Myelin and lymphocyte protein (MAL) is an integral membrane protein constituent of lipid rafts, and it is implicated in apical transport of proteins in polarized epithelial cells. However, beyond the involvement of MAL in apical sorting and as its function as a raft stabilizer, it is still not totally clear how MAL participates in cell proliferating processes. More controversial and interesting is the fact that MAL has been implicated in carcinogenesis in two opposite ways. First, this protein is overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…Moreover, some studies claimed that IL-1β could promote functional recovery, Schwann cell proliferation, and neurite outgrowth (Temporin et al, 2008;Nadeau et al, 2011). Emerging studies indicated that MAL was implicated in tumor promotion and suppression (Lara-Lemus, 2019). Importantly, overexpression of MAL could impede myelination in the PNS, which was consistent with our results (Buser et al, 2009;Schmid et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, some studies claimed that IL-1β could promote functional recovery, Schwann cell proliferation, and neurite outgrowth (Temporin et al, 2008;Nadeau et al, 2011). Emerging studies indicated that MAL was implicated in tumor promotion and suppression (Lara-Lemus, 2019). Importantly, overexpression of MAL could impede myelination in the PNS, which was consistent with our results (Buser et al, 2009;Schmid et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…It is clear is that the proposed role of MAL as a tumor suppressor does not extend to all types of cancer, and malignancies of hematological cell types in which MAL is endogenously expressed, and at least those of the ovarian epithelium, are specifically excluded. MAL may have a tumor suppressive role in some cancers and an oncogenic role in others [ 293 ]. However, there is no direct evidence of such an oncogenic role, since the link between high levels of MAL correlate and the poor prognosis of B-cell lymphomas and ovarian cancer [ 226 , 227 ] does not necessarily mean that MAL induces the transformation of normal cells in neoplastic cells.…”
Section: Mal In Cancermentioning
confidence: 99%
“…It participates in the apical transport of proteins in polarized epithelial cells [ 7 ]. The role of its abnormal expression in tumorigenesis and development has attracted increasing attention [ 8 ]. MAL is specifically expressed in different tissues and cells, and its expression level differs in different cells of normal gastric tissue [ 9 ].…”
Section: Introductionmentioning
confidence: 99%